Impact of age on host responses to diet-induced obesity: Development of joint damage and metabolic set points - Collins, Kelsey H.; MacDonald, Graham Z.; Hart, David A.; Seerattan, Ruth A.; Rios, Jaqueline L.; Reimer, Raylene A.; Herzog, Walter (Journal of sport and health science, 2020)
•Osteoarthritis (OA) is one of the leading causes of pain and disability worldwide, and a large percentage of patients with osteoarthritis are individuals with obesity.•Animals fed an obesity-inducing diet from adulthood had more knee joint damage when compared to both the control diet animals and animals fed a bad diet from a young age.•These findings indicate that dietary exposure time in young animals may induce less damage than exposure to bad diets during adulthood, indicating the importance of the onset of dietary challenge in studies that aim to assess the short-term influence of obesity-inducing diets on knee joint health. Osteoarthritis is one of the leading causes of pain and disability worldwide, and a large percentage of patients with osteoarthritis are individuals who are also obese. In recent years, a series of animal models have demonstrated that obesity-inducing diets can result in synovial joint damage (both with and without the superimposition of trauma), which may be related to changes in percentage of body fat and a series of low-level systemic inflammatory mediators. Of note, there is a disparity between whether the dietary challenges commence at weaning, representing a weanling onset, or at skeletal maturity, representing an adult onset of obesity. We wished to evaluate the effect of the dietary exposure time and the age at which animals are exposed to a high-fat and high-sucrose (HFS) diet to determine whether these factors may result in disparate outcomes, as there is evidence suggesting that these factors result in differential metabolic disturbances. Based on dietary exposure time, we hypothesized that rats fed an HFS diet for 14 weeks from weaning (HFS Weanling) would demonstrate an increase in knee joint damage scores, whereas rats exposed to the HFS diet for 4 weeks, starting at 12 weeks of age (HFS Adult) and rats exposed to a standard chow diet (Chow) would not display an increase in knee joint damage scores. Male Sprague-Dawley rats were fed either an HFS diet for 14 weeks from weaning (HFS Weanling) or an HFS diet for 4 weeks, starting at 12 weeks of age (HFS Adult). At sacrifice, joints were scored using the modified Mankin Criteria, and serum was analyzed for a defined subset of inflammatory markers (Interleukin-6, leptin, monocyte chemoattractant protein-1, and tumor necrosis factor α). When the HFS Weanling and HFS Adult groups were compared, both groups had a similar percent of body fat, although the HFS Weanling group had a significantly greater body mass than the HFS Adult group. The HFS Weanling and HFS Adult animals had a significant increase in body mass and percentage of body fat when compared to the Chow group. Although knee joint damage scores were low in all 3 groups, we found, contrary to our hypothesis, that the HFS Adult group had statistically significant greater knee joint damage scores than the Chow and HFS Weanling groups. Furthermore, we observed that the HFS Weanling group did not have significant differences in knee joint damage scores relative to the Chow group. These findings indicate that the HFS Weanling animals were better able to cope with the dietary challenge of an HFS diet than the HFS Adult group. Interestingly, when assessing various serum proinflammatory markers, no significant differences were detected between the HFS Adult and HFS Weanling groups. Although details regarding the mechanisms underlying an increase in knee joint damage scores in the HFS Adult group remain to be elucidated, these findings indicate that dietary exposure time maybe less important than the age at which an HFS diet is introduced. Moreover, increases in serum proinflammatory mediators do not appear to be directly linked to knee joint damage scores in the HFS Weanling group animals but may be partially responsible for the observed knee joint damage in the adults over the very short time of exposure to the HFS diet. [Display omitted]